The concept of the person in the philosophy of Robert Spaemann - Figueroa Gonzalez, Julia Isabel (2025)
The question about the meaning of being a person has been present throughout the history of humanity, with great concern arising in investigating the origin of the human being, the qualities that make it different from other living beings, among other concerns. For this reason, the present work aims to construct a general review of the concept of person, a central theme in the philosophy of Robert Spaemann. To do this, it is important to review his thought on topics about the nature of being, the reasons why he considers every man as a person and the exclusive qualities of this same one.